Allergen immunotherapy for house dust mite-induced rhinitis: prescriptive criteria - Ridolo, Erminia; Incorvaia, Cristoforo; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2021)
Allergic rhinitis (AR) is a very common disease. In most cases, therapy is based on symptomatic drugs, while allergen immunotherapy (AIT), which is the only one to act on the cause of the disease, is reserved for patients with a greater burden of disease. In particular, the possible evolution towards asthma substantiates the use of AIT, but requires the availability of diagnostic indices related to the risk of developing asthma. We analyzed the available literature on risk factors for onset of asthma in patients with AR, including bronchial hyperresponsiveness, uncovering by respiratory function tests of airway impairment, measurement of fractioned exhaled nitric oxide, given IgE sensitization pattern, and respiratory infections detected by nasal mucus samples or by particular microbiomes. Most of these risk predictors have been investigated too little or do not have consistent results, while various studies have confirmed that early bronchial impairment in AR patients, particularly concerning small airways, should be considered as prescriptive criteria for AIT.